REDEFINING THE CONCEPT OF ASCETICISM (ZUHD) IN TASAWWUF:ABUL HASAN ASH-SHADHILI’S VIEW AND HIS TARIQA SHADHILIYYA - anggraini, erlina (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2019)
Lots of the Muslims still consider that poverty is the way to get closer (taqarrub) toAllah the Most Beneficent. Such misunderstanding of Islamic teaching makes theMuslims do not have working motivation and desire. This study is a qualitative-basedresearch. It aims to investigate and focus on Abu Hasan al-Shadhili attitude regardingwealth and his perspective about it based on his deep insight on the Qur'an and hadith.The data were gained from library research to find complete information about Syeikhal-Shadhili and his Tariqa Shadhiliyah. The analysis of the data was carried outthrough descriptive analysis to reveal the collected information from some documents(books, journals, and websites). One thing that makes him different from other Sufi ishis concern with society, his sacrifice for people, and his country. According to him, ifall salik (man undergoing spiritual journey) who are honest and pious are only busywith their religious ritual and neglect their society, dishonest and greedy people willtake power and as a result, the Muslims would be neglectful of their worldly matters